(untitled) (Neliniini Kolyvannya, 2007)
In this paper, a fixed point theorem due to Schaefer combined with a selection theorem due to Bressan and Colombo [8] for lower semicontinuous multivalued operators with nonempty closed and decomposable values is used to investigate the existence of solutions for first and second order impulsive functional differential inclusions with variable times.